JARINGAN PENGANGKUT TANAMAN PEPAYA (Carica papaya L.) YANG TUMBUH PADA TANAH TINGGI ALUMUNIUM - Nyonita Punjungsari, Tyas; Ulfa, Fitria (Universitas Islam Balitar, 2022)
Purpose of this study is to determine the anatomical differences of transport tissue (xylem and phloem) in Carica papaya L. Roots, which grown on contaminated and uncontaminated Al (Aluminum). The study was carried out by digging 0-30 cm of soil to take 3 lateral roots, then cut transversely, stained using xylol and observed the transport tissue using a computer binocular microscope with a magnification of 100x. Based on the research, it is known that the xylem and phloem of transport tissue obtained from the roots of Carica papaya L. which grows on soil contaminated with aluminum slag ash has differences with the root transport tissue of Carica papaya L. which grows on soil without aluminum slag ash contamination.